Virtual reality simulation for nursing education: effectiveness and feasibility - Debra Kiegaldie; Louise Shaw (BMC, 2023)
Abstract Virtual Reality simulation (VRS) is an innovative and emerging technology that has the potential to offer increased numbers of pre-registration students authentic learning experiences compared to traditional simulation- based education (SBE) with simulated participants. The aim was to evaluate learner outcomes of SBE compared to 4 fully immersive VRS scenarios, for vocational and higher education nursing students at a training and further education institute in Melbourne, Australia. A mixed methods quasi-experimental design study was conducted over two semesters from 2019 to 2020. Participants were 675 pre-registration nursing students. The intervention group (VRS n = 393) received 4 three-dimensional, immersive VRS modules. The control group (SBE n = 282) received 4 face-to-face large group immersive simulations. In the VRS group 95% of students actively participated, compared to SBE (on average 15%). Knowledge test scores were initially significantly greater (p < 0.01) for VRS versus SBE students, but not maintained post clinical placement. Intervention students found VRS to be realistic and prepared them for clinical practice. Some technical difficulties were identified with VRS. VRS was found to be more cost effective than SBE. VRS fostered critical thinking and provided an efficient and sustainable platform for learning about complex clinical situations.